The Become a Profit Maker and Profit Keeper Against the Moral Responsibilities of Private University Lecturers - Billy Josef Anis (MASTER: Jurnal Manajemen Strategik Kewirausahaan, 2021)
Purpose – The purpose of this paper is to design implementation for two employee categories (A and B) model profit as lecturer’s moral responsibility as part as an employee of the private university. Design / methodology/approach - This paper uses a case study approach to analyze the implementation of profit maximization in private industries such as financial services, to be applied in the private higher education industry to face open competition, especially corporate universities. Findings - The results of the research find that there is a positive and significant relationship between profit maker and profit keeper are in line with the moral responsibility of private lecturers. Limitations/implications - Research is very limited on owner respondents, and there is no measurement transparency model. It is a challenging implication for further research. Practical Implications – This research will be useful for applied research. The investment must be profitable. Student consumers must be looked after. Industries are transforming rapidly due to competition, market share, and avoiding failure. The model strategy should be run as a profit-oriented industry. Originality / value – The research contributes greatly to professional models for private owners and lecturers, also provides a collaboration formula for sustainable competitive strategies from the start of investment to how it becomes more profitable.